2020
DOI: 10.1111/mec.15686
|View full text |Cite
|
Sign up to set email alerts
|

Genomic basis of the loss of diadromy inGalaxias maculatus: Insights from reciprocal transplant experiments

Abstract: Diadromy is known for having major effects on the distribution and richness of aquatic species, and so does its loss. The loss of diadromy has led to the diversification of many species, yet research focusing on understanding its molecular basis and consequences are limited. This is particularly true for amphidromous species despite being the most abundant group of diadromous species. Galaxias maculatus, an amphidromous species and one of the most widely distributed fishes in the Southern Hemisphere, exhibits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 89 publications
3
21
0
Order By: Relevance
“…2020) and for understanding the basis of reproductive isolation among recently diverged lineages (Delgado et al . 2020).…”
Section: Introductionmentioning
confidence: 99%
“…2020) and for understanding the basis of reproductive isolation among recently diverged lineages (Delgado et al . 2020).…”
Section: Introductionmentioning
confidence: 99%
“…(2019) Populations diversity and structure Galaxias maculatus Yes Delgado et al. (2019) Salinity adaptation Galaxias maculatus Yes Delgado et al. (2020) Transcriptomics (transcriptome sequencing) Salinity adaptation Plecoglossus altivelis Yes Lu et al.…”
Section: Introductionmentioning
confidence: 99%
“…Reciprocal transplant experiments with common galaxias under laboratory conditions also revealed that resident populations can differ in their response to salinity changes with some populations maintaining their osmoregulatory performance necessary for migration and others not being able to survive such changes ( Delgado et al., 2020 ). Given that these populations were similarly genetically differentiated from their diadromous counterpart, we suspect genetic drift may be one of the factors playing an important role in determining whether the ability to migrate is maintained or lost.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amphidromy is the most frequent among diadromous migratory strategies 11 and was classically described as spawning in freshwater riverine habitats with subsequent larvae transport downstream and development in marine habitats, and juvenile migration back to freshwater habitats to complete growth to adults 12 . However, recent studies have shown that some populations of amphidromous species may lose migratory traits and develop resident populations 13,14 . These facultative amphidromous fish species are characterised by a complex pattern of migratory and resident…”
mentioning
confidence: 99%